Dynamic event-based finite-horizon H∞ secure consensus control of a class of nonlinear multi-agent systems - Pang, Kai; Ma, Lifeng; Bai, Hongyang; Yi, Xiaojian (ISA transactions, 2022)
In this paper, we investigate the H∞ consensus control issue for nonlinear multi-agent systems (MASs) subject to multiple attacks over a finite time interval. A novel and comprehensive model to characterize the multiple attacks is presented that includes denial-of-service (DoS) attacks, scaling attacks and replay attacks. With the hope of easing the communication burdens, we implement a dynamic event-triggered scheme to schedule the process of data sharing among the individual subsystems, which helps judge if the collected data should be shared to neighboring agents for control input update. The aim of the proposed problem is to develop an output feedback strategy to meet the desired H∞ consensus performance despite the existence of multiple attacks. Some conditions are presented for the solvability of the investigated problem, and the feedback gains are obtained via certain convex optimization algorithms. The proposed theoretical result is finally demonstrated by virtue of two illustrative simulation examples. •A multiple attacks model is constructed.•A DETM is adopted for each agent to relieve the communication burden.•The corresponding finite-horizon H∞ performance index is defined.